Peran Komite Madrasah dalam Penguatan Hubungan Sekolah dan Masyarakat - Anwar Hidayat; Romlah; Oki Dermawan (Kartika: Jurnal Studi Keislaman, 2026)
The role of school committees is essential in strengthening school–community relations and improving educational quality. This study aims to analyze and describe the role of school committees in enhancing community relations at MIN 6 and MIN 9 Bandar Lampung. This research employed a qualitative descriptive approach, with data collected through interviews and documentation. The findings indicate that school committees at both institutions have performed their functions relatively effectively through four main roles: (1) advisory agency in curriculum policy formulation and budget planning, (2) supporting agency in providing financial, intellectual, and human resource assistance, (3) controlling agency in monitoring program implementation and evaluation, and (4) mediator agency in facilitating communication between schools and the community. Nevertheless, several challenges remain, particularly related to limited financial resources and the need for improved coordination in community engagement. These findings suggest that the effectiveness of school committees is closely associated with member capacity, transparency in communication, and sustained commitment from educational stakeholders.